The Third Way to Adult Education - Judith Walker (Adult Education Research Conference, 2006)
This paper examines how Third Way politics play out in policy discourse in adult education in Canada and New Zealand. It then places these findings in the larger context of the debates on “second modernity.”
Keywords: Third Way; policy; Canada; New Zealand; globalization